Organized Online Learning of Students in Universities and Schools: Didactics and Methodology - Gadzaova, Lyudmila Petrovna (2021)
This article discusses the urgent aspects of online learning didactics. They are comprised of, for instance, organization and methods of organized learning, main principles of actions aimed at practical orientation; their objective is combination of the methods of distance learning, formation of efficient skills of students with social mediation, analysis of reasons of errors and their correction, pursuance of success in relevant areas. Organized online learning also provides opportunity for students to use all advantages of digital technologies: flexibility, individual distribution of learning duration, compatibility with other forms of occupation. In addition to digital know-how, organization of learning and independent work of distant students can develop self-discipline, sustainability of acquired skills. Students can use various digital sources of information available under various conditions in addition to that organized under the management of distance learning teacher.